RANCANGAN DAN PENERAPAN MEDIA SOSIAL INSTAGRAM @PITEK_NDESO SEBAGAI MEDIA PROMOSI PADA PITEK NDESO CATERING TUBAN - Ghefira Nurfadhila (Jurnal Bisnis Terapan, 2024)
In this digital era, technology and information have become an integral part of Indonesian life. This opens up new opportunities for businesses, including culinary businesses, to carry out effective and efficient promotional strategies. One example is Pitek Ndeso Catering in Tuban, which utilizes Instagram social media to reach consumers widely. Pitek Ndeso uses various Instagram features such as feeds, stories, and highlights to promote its products. However, the Instagram feed design used by Pitek Ndeso is not yet able to support Pitek Ndeso's brand promotion activities online. The purpose of this research is to design digital promotional media in the form of Instagram feeds and stories to increase brand awareness of Pitek Ndeso Catering. The research method used is qualitative using the Marketing 5.0 approach. in the design process, it is carried out through three stages of visualization, namely, sketching, editing, and final design. The results of this research are in the form of 12 Instagram feed designs, 5 Instagram stories and insight data after implementing a content design strategy. The content used in the design includes product content, interesting facts, minigames, and filler content. Copyright © 2024 by Authors, Published by Jurnal Bisnis Terapan. This work is licensed under a Creative Commons. Attribution-ShareAlike 4.0 International License